Dampak Penerapan Job Order Costing Terhadap Profitabilitas Perusahaan (Studi Kasus pada Percetakan Jaya Record Kediri: Studi Kasus Pada Percetakan Jaya Record Kediri - Irfan Daffa Dwi Putra; Beby Hilda Agustin; Miladiah Kusumaningarti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
This study aims to analyze the impact of the implementation of the job order costing method on company profitability, with a case study at Percetakan Jaya Record Kediri. The background of this research is based on the importance of accurate cost of goods manufactured (COGM) calculation in supporting selling price determination and profitability measurement. The research method used is descriptive quantitative, with data obtained from production cost reports, job cost sheets, and income statements for the period of January–May 2024. The results show a difference in cost of goods manufactured of Rp10,936,470 between the company’s method and the job order costing method. This difference affects the net profit margin (NPM), where the company’s method produces an NPM of 13.55%, while the job order costing method results in an NPM of 13.80%. Furthermore, the more accurate cost of goods manufactured calculation using the job order costing method can be used as a basis for determining selling prices through the cost plus pricing method, by adding the expected profit margin above production costs. The implementation of this method assists the company in setting more rational and competitive selling prices while ensuring the desired level of profit. These findings indicate that the application of the job order costing method provides more accurate cost information and has a positive impact on company profitability, serving as a reference for management in cost control, pricing decisions, and strategic decision-making.